2015
DOI: 10.2495/esus150151
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability to energy, production efficiency and the crude oil price: evidence from a small open economy

Abstract: Taiwan is an economy which is highly dependent on energy imports. A change in oil price not only affects the cost of production, but also the economic growth. Since the year 2000, the crude oil price has risen and become an unstable factor for economic development. In response to the rapid rising of emerging economies and the competitive international economic environment, Taiwan is facing a moment of industrial restructuring. Energy-saving technologies and improved efficiency might play important roles. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In particular, the study of the adaptability of the economy to the change in the prices of crude oil by the example of Taiwan [84], the USA [85], China [86], Malaysia [87] and other countries [8] are of considerable interest for scientists. It is important to note that in certain works [84,85] results are presented according to the branches of the economy. At the same time, in our opinion, the methodical approaches to quantitative assessment of the level of adaptation of the economies to changes in energy prices and to risks of energy markets require further development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, the study of the adaptability of the economy to the change in the prices of crude oil by the example of Taiwan [84], the USA [85], China [86], Malaysia [87] and other countries [8] are of considerable interest for scientists. It is important to note that in certain works [84,85] results are presented according to the branches of the economy. At the same time, in our opinion, the methodical approaches to quantitative assessment of the level of adaptation of the economies to changes in energy prices and to risks of energy markets require further development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This Journal is licensed under a Creative Commons Attribution 4.0 International License hinges excessively on energy consumption (Bruno and Sachs, 1985;Hamilton, 1983;Davis and Haltiwanger, 2001;Lee, et al, 2002;Hong and Hsu., 2018). Therefore, the stability of energy prices does not only affect production costs but also constitutes a vital factor influencing economic development (Huang et al, 2015a;2015b). How to achieve economic development given these conditions in Taiwan warrants discussion?…”
Section: Numerous Studies Have Shown That Energy Price Fluctuations Can Cause Tremendous Economic Loss When Economic Growthmentioning
confidence: 99%
“…Improved productivity can increase profits by reducing energy consumption while achieving the objective of economic growth (Heintz et al, 2009;Ramey, 2011). Huang et al (2015a;2015b) found that following its entry into the World Trade Organization, Taiwan has exhibited increasingly high imported-energy intensity and considerably heightened sensitivity to energy prices, implying the Taiwanese economy has become more restricted by its reliance on energy. Achieving sustainable economic development in a country necessitates advances in R&D technologies and equipment investment, which enable a country to adapt to changes in the international economic environment and realize industrial restructuring (Hong et al, 2017).…”
Section: Numerous Studies Have Shown That Energy Price Fluctuations Can Cause Tremendous Economic Loss When Economic Growthmentioning
confidence: 99%